The coordination variability of 'traditional' and 'specific' sprint training exercises compared to high speed running - Pennels, T.; White, J.; Wilson, C.; Irwin, G.; Exell, T. (ISBS Proceedings Archive (Michigan), 2022)
This study aimed to compare specificity of three different resistance training exercises (Back Squat (BS), Bulgarian Split Squat (BSS), and Single-Leg Romanian Deadlift (SL-RDL) compared to high speed running (HSR). Three-dimensional kinematic data were collected from 6 males (age 22.2 ± 1.6 years, height 1.85 ± 0.05 m, mass 77.55 ± 6.50 kg) who completed two sets of six repetitions with two repetitions in reserve for each resistance training exercise and two 10 second treadmill runs at 20 kph (5.56 m/s). Kinematic results from the hip, knee and ankle (max. flexion, max. extension, and range of motion) revealed there was not an exercise that was consistently similar to HSR. Coordination profiling revealed the BS exercise had similarities to HSR across all three joints, however the BSS did show greater specificity at the hip.